Endoscopy and magnetic resonance imaging in patients with Crohn's disease: a retrospective single-centre comparative study - Dinter, Dietmar; Chakraborty, Anja; Brade, Joachim; Back, Walter; Neff, Wolfgang; Singer, Manfred V.; Böcker, Ulrich (Scandinavian journal of gastroenterology, 2008)
Objective. There is ongoing debate about which imaging modality is best for patients with inflammatory bowel diseases. Magnetic resonance imaging (MRI) has been successfully used to evaluate the jejunum and the ileum. Because virtual colonoscopy by MRI requires bowel cleansing and/or rectal filling, endoscopy is preferred for assessment of the colon. However, hydro-MRI without special bowel preparation may be sufficient as a diagnostic tool if specifically targeted in the course of a known disease. The aim of this study was retrospectively to assess the correlation of endoscopy, histology and MRI findings for the terminal ileum and the colon in a cohort of patients with Crohn's disease. Material andmethods. In all, 60 patients with a confirmed diagnosis of Crohn's disease were included in the study. Here, 412 anatomical segments of the colon were analysed by MRI, 401 by endoscopy and 374 by histology. Results. Presence or absence of inflammation was concordantly diagnosed in 310 segments (77.3%). The highest concordance was found for the terminal ileum and, in patients with previous surgery, the anastomosis. Sensitivity and specificity for MRI versus endoscopy, MRI versus histology and endoscopy versus histology were 64.4%/81.1%, 62.1%/86.2% and 78.2%/80.3%, respectively. Conclusions. In a retrospective analysis of patients with Crohn's disease, hydro-MRI assessment of inflammation in anatomical segments of the colon reaches acceptable concordance rates with endoscopy and histology without prior preparation of the bowel. The data justify a prospective controlled trial.